THE EFFECTIVENESS OF PLAYING METHODS IN IMPROVING PHYSICAL EDUCATION LEARNING OUTCOMES (INDONESIA) - pringgo mardesia (Program Pascasarjana Universitas Negeri Jakarta, 2020)
This study aims to see the effectiveness of the playing methodin improving physical education learning outcomes. The playing method can be given to students in order to understand and explain the learning material. When using thethe playing method can introduce various levels of tasks / material to be carried out. Where the playing method assigns different tasks in levels. The use of the playing method can encourage students to determine their level of performance in carrying out the physical education learning process.This article providesincrease on physical education learning outcomes, with difference in mean = 7.06, which means the difference in learning outcomes scores physical education between after and before given the playing method. The positive price was significant after being given the play method with the physical education learning outcomes score higher than before the playing method was given. Furthermore, the results in this study are the statistical price t =20,276, where db = 43 and the number sig. or p-velue = 0.000 <0.05 or H0 is rejected. Thus, it can be concluded that the method of playing provides positive results on students' physical education learning outcomes. Because by playing students can develop creativity, physical, motor, perception, cognitive, and social personal.